2020
DOI: 10.3390/educsci10020034
|View full text |Cite
|
Sign up to set email alerts
|

How Should Chemistry Educators Respond to the Next Generation of Technology Change?

Abstract: Chemical educators are facing a new generation of instructional technologies that impact classroom teaching. New technologies, like smartphones, cloud computing and artificial intelligence take learning beyond the classroom; 3D printing, virtual reality, and augmented reality provide new ways to teach the virtualization skills that are important for chemists. These technologies cause students to become more isolated, so students may not develop the social skills that they will need for today's workplace. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…30 Over the past decade years smartphones have become more and more prevalent in the school day. It has been suggested that they can be a useful tool in chemistry to learn the naming of organic chemical compounds, 31 to use them in analytical chemistry for optical and electrochemical detection and chemometric applications, 32 for quantifying gold-nanoparticle concentrations, 33 for pH determination, 34 many students need the smartphone camera to make videos of demonstrations, to copy complex diagrams from the blackboard 35 etc. In addition, chemistry apps such as Chemdoodle, Periodic Table, Chemistry Helper, Reaction Flash, Learn IUPAC Nomenclature, Chemical Solution Calculator and many others whose target audience is students, chemistry professionals, and teachers, provide them with powerful and compact tools to solve problems conveniently and free themselves from traditional media, heavy books, and bulky computers.…”
Section: Discussionmentioning
confidence: 99%
“…30 Over the past decade years smartphones have become more and more prevalent in the school day. It has been suggested that they can be a useful tool in chemistry to learn the naming of organic chemical compounds, 31 to use them in analytical chemistry for optical and electrochemical detection and chemometric applications, 32 for quantifying gold-nanoparticle concentrations, 33 for pH determination, 34 many students need the smartphone camera to make videos of demonstrations, to copy complex diagrams from the blackboard 35 etc. In addition, chemistry apps such as Chemdoodle, Periodic Table, Chemistry Helper, Reaction Flash, Learn IUPAC Nomenclature, Chemical Solution Calculator and many others whose target audience is students, chemistry professionals, and teachers, provide them with powerful and compact tools to solve problems conveniently and free themselves from traditional media, heavy books, and bulky computers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several researchers are also interested in using mix-methods (4 articles). Another interesting thing is the augmented reality trend which is approached by R&D. -Muqbil, 2022;Cahyana et al, 2023;Cejka et al, 2021;Chuang et al, 2023;Kumar et al, 2023;López-Cortés et al, 2021;Petrov & Atanasova, 2020;Wang et al, 2022) 2 Qualitative 21 (Abriata, 2020;Aivelo & Uitto, 2016;Annisa & Subiantoro, 2022;Borrel & Fourches, 2017;Bouksim et al, 2018;Bursjöö, 2022;Celik et al, 2020;Cortés Rodríguez et al, 2022;Fuchsova & Korenova, 2019;Gregorcic & Torkar, 2022;Lam et al, 2023;Loucif et al, 2019;Maraza-Quispe et al, 2023;Nasharuddin et al, 2021;Nuanmeesri, 2018;Pence, 2020;Reeves et al, 2021;Rodríguez et al, 2021;Saidin et al, 2015;Stojšić et al, 2022).…”
Section: Research Types/methodsmentioning
confidence: 99%
“…Cause universities do not pay for and maintain expensive hardware on-site anymore. Just use it through cloud providers such as Amazon, Google, or Microsoft; it means no longer needed that their computers (Pence, 2020).…”
Section: Introductionmentioning
confidence: 99%